Cardiovocal syndrome (Ortner syndrome) associated with secondary pulmonary arterial hypertension in a patient with mixed connective tissue disease. Issue 1 (2nd January 2018) - Hirata, Manami; Sunahori-Watanabe, Katsue; Isihara, Miyuki; Shibuto, Nobuyuki; Hiramatsu, Sumie; Miyawaki, Yoshia; Morishita, Michiko; Ohashi, Keiji; Katsuyama, Eri; Watanabe, Haruki; Kawabata, Tomoko; Sada, Ken-Ei; et al.
Abstract: Cardiovocal syndrome (Ortner syndrome) is characterised by a vocal hoarseness due to a left recurrent laryngeal nerve (LRLN) paralysis caused by a mechanical compression of the nerve by enlarged cardiovascular structures in various cardiovascular diseases. Here, we describe a rare laryngeal complication associated with secondary pulmonary arterial hypertension (PAH) in a patient with mixed connective tissue disease (MCTD). A 23-year-old woman who presented with hoarseness was diagnosed left vocal cord palsy by laryngofiberscopy. Further examination revealed that a secondary PAH associated with a MCTD was most likely to the cause of LRLN paralysis. Although the pulmonary artery pressure itself was rapidly normalised after the initiation of treatment with immunosuppressants and vasodilators, it took over a year for the dilation of pulmonary artery trunk as well as vocal cord palsy to improve. Laryngeal involvement is a rare complication of autoimmune diseases such as systemic lupus erythematosus (SLE) and MCTD. The identification of the cause behind the genesis of a laryngeal complication and the immediate initiation of an intensive treatment together is important to improve vocal cord palsy associated with systemic autoimmune disorders.